(untitled) (Research, Society and Development, 2021)
This is a protocol for a systematic review (intervention). Electrical stimulation (ES) is a therapeutic strategy used to improve peripheral nerve regeneration that involves the application of electrical fields of constant or varying frequency. We are going to lead a literature search to identify all published and unpublished randomized controlled trials that describe the use of ES in patients with peripheral nerve injury. We will compare: Electrical stimulation (application of electrical fields of constant or varying frequency) versus sham in patients with peripheral nerve injury; Electrical stimulation versus standard treatment (physiotherapy) in patients with peripheral nerve injury; Electrical stimulation versus no treatment in patients with peripheral nerve injury. Considering the scenario of very numerous strategies and different techniques of ES to stimulate nerve regeneration, decisions to recommend them should consider these uncertainties and should be summarized intended its application in clinical practice. The objective of this review is to assess the influence of electrical stimulation (ES) on nerve regeneration in individuals with peripheral nerve injury.